2023
DOI: 10.1038/s41541-023-00644-8
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Respiratory Papillomatosis (RRP)—Meta-analyses on the use of the HPV vaccine as adjuvant therapy

Abstract: Recurrent Respiratory Papillomatosis(RRP) is a rare disease with severe morbidity. Treatment is surgical. Prevailing viewpoint is that prophylactic HPV vaccines do not have therapeutic benefit due to their modus operandi. Studies on HPV vaccination alongside surgery were meta-analysed to test effect on burden of disease. Databases were accessed Nov and Dec 2021 [PubMed, Cochrane, Embase and Web of Science]. Main outcome measured was: Mean paired differences in the number of surgeries or recurrences per month. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…, reported an increase in intersurgical intervals following vaccination with Gardasil ® , thereby highlighting the benefit of Gardasil ® as adjuvant therapy in JoRRP. 12,13 Our study showed a minor overall increase in intersurgical time intervals; the most significant increase was observed in the patients with more severe disease, with an average of 2.8 to 9 months intersurgical intervals following three doses of the Gardasil ® . In addition, 16/25 patients (64%) received at least one dose of Gardasil ® in their 1st year of the disease, with many patients showing an improvement in their DC scores in their first year.…”
Section: Discussionmentioning
confidence: 64%
“…, reported an increase in intersurgical intervals following vaccination with Gardasil ® , thereby highlighting the benefit of Gardasil ® as adjuvant therapy in JoRRP. 12,13 Our study showed a minor overall increase in intersurgical time intervals; the most significant increase was observed in the patients with more severe disease, with an average of 2.8 to 9 months intersurgical intervals following three doses of the Gardasil ® . In addition, 16/25 patients (64%) received at least one dose of Gardasil ® in their 1st year of the disease, with many patients showing an improvement in their DC scores in their first year.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, the reduction of recurrences after treatment in vaccinated patients is also confirmed for benign lesions [111][112]. In fact, for respiratory papillomatosis the substantial benefit is known for HPV vaccination used as adjunctive therapy in combination with surgery [113]. In contrast, vaccination does not seem to provide a significantly secondary benefit in patients with previous ano-genital warts, also this cannot be generalized due to the few randomized controlled trials performed [114].…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…In a non-randomised trial, patients with newly diagnosed or established RRP were vaccinated, and both groups showed a reduced frequency of RRP and a reduced disease burden [ 79 ]. A meta-analysis of HPV vaccination in RRP cases alongside surgery indicated that vaccination is a beneficial adjunct therapy alongside surgery [ 80 ]. Treatment with GARDASIL9 ® has positively affected five cases of recalcitrant genital warts [ 81 ].…”
Section: Hpv Vaccination Of People With Hpv-associated Diseasementioning
confidence: 99%